Why a New Journal in Classical Numismatics?: The Rationale for KOINON and Some Introductory Comments - Molinari, Dr Nicholas J. (KOINON: The International Journal of Classical Numismatic Studies, 2018)
I had the great benefit of reading some dystopian novels during my summer graduate work, specifically Aldous Huxley’s Brave New World and George Orwell’s 1984. Initially, when I sat down to write this brief introduction and welcome message to KOINON, I laid out a grand philosophical justification for its existence based on the lessons from these two works. In the final analysis, it was just ok (it was actually a bit much, if I’m being honest). We all know that totalitarianism is a danger even now and that many attempts have been made throughout history at erasing the past, so there is really no need for me to go on and on about it. And, likewise, we all also know that rampant consumerism à la Brave New World will ultimately destroy us, so we need to take time and appreciate things instead of always moving on to the next thing, coins included. KOINON was, in my initial speculations, a noble attempt at keeping historic scholarship alive and well in the face of unprecedented social progress, all through the study of numismatics. Moreover, by participating in the journal, we would all make the world a better place. While there is not anything particularly wrong with that sort of justification, it ignores the real reason for KOINON, namely, the fact that I love studying and writing about ancient coins, and so do many of you. Ultimately, then, the real purpose of KOINON is to offer a venue for taking a closer look at the past, because so much knowledge about antiquity can be regained through the study of numismatics. This journal is here to help people do precisely that.